My Voice Matters: Jacobs, L.J. (2024). Rocklands: On Becoming the First Generation of Black Psychologists in Post-Apartheid South Africa. Cape Town: African Minds. 157 pages. ISBN (paper): 978-1-928502-89-0. - Arendse, Danille (PINS-Psychology in Society, 2025)
Apartheid created a system of violence, in which violence was not only transmitted against the state, but also within families in different forms. In the unfolding of the everyday racism that Black academics need to endure to survive and thrive in academic institutions. It is evident thatthe oppressor’s generational transfer of racism persists, forcing Black people to resist. This is hard and exhausting labour forced upon Black bodies as part of their survival in academic spaces. Since racism and other forms of oppression continue to shape the lives of Black academics, it becomes necessary to revisit the past. Through the re-examining of the past, we can critically engage with the subtle warnings before us that the past may continue to repeat itself in the present, inevitably impacting our sense of belonging. It is through this re-examination of the past that Liezille Jacobs’ book, Rocklands: On Becoming the First Generation of Black Psychologists in Post-Apartheid South Africa, becomes a powerful testimony of resistance and refusal.